New combination and new synonym in Paedarium Aldrich, 1926 (Diptera: Tachinidae) - Toma, Ronaldo (Entomological Communications, 2023)
Voria pollyclari (Rocha-e-Silva, Lopes & Della Lucia, 1999) is moved to Paedarium Aldrich, 1926 and simultaneously synonymized under Paedarium subauratum (Blanchard, 1943): Paedarium pollyclari, comb. nov., syn. nov.